2016
DOI: 10.1542/peds.2015-3482
|View full text |Cite
|
Sign up to set email alerts
|

Birth Spacing and Risk of Autism and Other Neurodevelopmental Disabilities: A Systematic Review

Abstract: CONTEXT: Both short and long interpregnancy intervals (IPIs) have recently been associated with increased risk of autism spectrum disorder (ASD). However, this association has not been systematically evaluated.OBJECTIVE: To examine the relationship between birth spacing and the risk of ASD and other neurodevelopmental disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 64 publications
(87 reference statements)
2
32
0
Order By: Relevance
“…16 However, the WHO guidelines are now more than 13 years old, and more recently issued guidance by healthcare organisations have suggested an interval of 18-24 months following a previous live birth may be optimal. [16][17][18] Previously published reviews have evaluated the impact of short IPI on neurodevelopmental disabilities and 19 nutritional status, 20 and the effect of IPI after a previous miscarriage on birth outcomes. 21 A recent systematic review of research from high-income countries (HICs) identified three studies evaluating the association between short IPI and perinatal death.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the WHO guidelines are now more than 13 years old, and more recently issued guidance by healthcare organisations have suggested an interval of 18-24 months following a previous live birth may be optimal. [16][17][18] Previously published reviews have evaluated the impact of short IPI on neurodevelopmental disabilities and 19 nutritional status, 20 and the effect of IPI after a previous miscarriage on birth outcomes. 21 A recent systematic review of research from high-income countries (HICs) identified three studies evaluating the association between short IPI and perinatal death.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-study in pediatrics, the effects of birth spacing on one facet of personality were taken into consideration. Conde-Agudelo et al (2016) analyze the noncausal relationships of the birth gap and autism. Their conclusion is that short birth intervals are associated with an increased risk of autism spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…For this latter set of analyses, we separately examined subsets with an inter-pregnancy interval (IPI) of 18–59 months and an IPI of 60+ months. We did not combine these two groups because IPI of 60+ months has itself been found to be associated with ASD risk (Conde-Agudelo et al 2016). …”
Section: Methodsmentioning
confidence: 99%